Mutation Distribution and Type Suggests Genetic Differences between the Etiology of Orofacial Clefting and Gastric Cancer. - Selvanathan, Arthavan; Nixon, Cheng Yee; Zhu, Ying; Scietti, Luigi; Forneris, Federico; Uribe, Lina M Moreno; Lidral, Andrew C; Jezewski, Peter A; Mulliken, John B; Murray, Jeffrey C; Buckley, Michael F; Cox, Timothy C; et al. (Genes (Basel), 2020)
Pathogenic variants in , encoding epithelial cadherin (E-cadherin), have been implicated in hereditary diffuse gastric cancer (HDGC), lobular breast cancer, and both syndromic and non-syndromic cleft lip/palate (CL/P). Despite the large number of mutations described, the nature of the phenotypic consequence of such mutations is currently not able to be predicted, creating significant challenges for genetic counselling. This study collates the phenotype and molecular data for available variants that have been classified, using the American College of Medical Genetics and Genomics criteria, as at least 'likely pathogenic', and correlates their molecular and structural characteristics to phenotype. We demonstrate that variant type and location differ between HDGC and CL/P, and that there is clustering of CL/P variants within linker regions between the extracellular domains of the cadherin protein. While these differences do not provide for exact prediction of the phenotype for a given mutation, they may contribute to more accurate assessments of risk for HDGC or CL/P for individuals with specific variants.
Keywords: Antigens, CD; Brain; Cadherins; Cleft Lip; Cleft Palate; Female; Genetic Counseling; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Male; Pedigree; Phenotype; Stomach Neoplasms

Mutations in GDF11 and the extracellular antagonist, Follistatin, as a likely cause of Mendelian forms of orofacial clefting in humans. - Cox, Timothy C; Lidral, Andrew C; McCoy, Jason C; Liu, Huan; Cox, Liza L; Zhu, Ying; Anderson, Ryan D; Moreno Uribe, Lina M; Anand, Deepti; Deng, Mei; Richter, Chika T; Nidey, Nichole L; et al. (Hum Mutat, 2019)
Cleft lip with or without cleft palate (CL/P) is generally viewed as a complex trait with multiple genetic and environmental contributions. In 70% of cases, CL/P presents as an isolated feature and/or deemed nonsyndromic. In the remaining 30%, CL/P is associated with multisystem phenotypes or clinically recognizable syndromes, many with a monogenic basis. Here we report the identification, via exome sequencing, of likely pathogenic variants in two genes that encode interacting proteins previously only linked to orofacial clefting in mouse models. A variant in GDF11 (encoding growth differentiation factor 11), predicting a p.(Arg298Gln) substitution at the Furin protease cleavage site, was identified in one family that segregated with CL/P and both rib and vertebral hypersegmentation, mirroring that seen in Gdf11 knockout mice. In the second family in which CL/P was the only phenotype, a mutation in FST (encoding the GDF11 antagonist, Follistatin) was identified that is predicted to result in a p.(Cys56Tyr) substitution in the region that binds GDF11. Functional assays demonstrated a significant impact of the specific mutated amino acids on FST and GDF11 function and, together with embryonic expression data, provide strong evidence for the importance of GDF11 and Follistatin in the regulation of human orofacial development.

Mutations in the Epithelial Cadherin-p120-Catenin Complex Cause Mendelian Non-Syndromic Cleft Lip with or without Cleft Palate. - Cox, Liza L; Cox, Timothy C; Moreno Uribe, Lina M; Zhu, Ying; Richter, Chika T; Nidey, Nichole; Standley, Jennifer M; Deng, Mei; Blue, Elizabeth; Chong, Jessica X; Yang, Yueqin; Carstens, Russ P; et al. (Am J Hum Genet, 2018)
Non-syndromic cleft lip with or without cleft palate (NS-CL/P) is one of the most common human birth defects and is generally considered a complex trait. Despite numerous loci identified by genome-wide association studies, the effect sizes of common variants are relatively small, with much of the presumed genetic contribution remaining elusive. We report exome-sequencing results in 209 people from 72 multi-affected families with pedigree structures consistent with autosomal-dominant inheritance and variable penetrance. Herein, pathogenic variants are described in four genes encoding components of the p120-catenin complex (CTNND1, PLEKHA7, PLEKHA5) and an epithelial splicing regulator (ESRP2), in addition to the known CL/P-associated gene, CDH1, which encodes E-cadherin. The findings were also validated in a second cohort of 497 people with NS-CL/P, comprising small families and singletons with pathogenic variants in these genes identified in 14% of multi-affected families and 2% of the replication cohort of smaller families. Enriched expression of each gene/protein in human and mouse embryonic oro-palatal epithelia, demonstration of functional impact of CTNND1 and ESRP2 variants, and recapitulation of the CL/P spectrum in Ctnnd1 knockout mice support a causative role in CL/P pathogenesis. These data show that primary defects in regulators of epithelial cell adhesion are the most significant contributors to NS-CL/P identified to date and that inherited and de novo single gene variants explain a substantial proportion of NS-CL/P.
Keywords: Alleles; Amino Acid Sequence; Animals; Biotinylation; Cadherins; Catenins; Cleft Lip; Cleft Palate; Epithelium; Female; Gene Deletion; Genetic Predisposition to Disease; Humans; Infant; Infant, Newborn; Male; Mice; Mutation; Palate; Pedigree; Syndrome; Whole Exome Sequencing

MECR Mutations Cause Childhood-Onset Dystonia and Optic Atrophy, a Mitochondrial Fatty Acid Synthesis Disorder. - Heimer, Gali; Kerätär, Juha M; Riley, Lisa G; Balasubramaniam, Shanti; Eyal, Eran; Pietikäinen, Laura P; Hiltunen, J Kalervo; Marek-Yagel, Dina; Hamada, Jeffrey; Gregory, Allison; Rogers, Caleb; Hogarth, Penelope; et al. (Am J Hum Genet, 2016)
Mitochondrial fatty acid synthesis (mtFAS) is an evolutionarily conserved pathway essential for the function of the respiratory chain and several mitochondrial enzyme complexes. We report here a unique neurometabolic human disorder caused by defective mtFAS. Seven individuals from five unrelated families presented with childhood-onset dystonia, optic atrophy, and basal ganglia signal abnormalities on MRI. All affected individuals were found to harbor recessive mutations in MECR encoding the mitochondrial trans-2-enoyl-coenzyme A-reductase involved in human mtFAS. All six mutations are extremely rare in the general population, segregate with the disease in the families, and are predicted to be deleterious. The nonsense c.855T>G (p.Tyr285), c.247_250del (p.Asn83Hisfs4), and splice site c.830+2_830+3insT mutations lead to C-terminal truncation variants of MECR. The missense c.695G>A (p.Gly232Glu), c.854A>G (p.Tyr285Cys), and c.772C>T (p.Arg258Trp) mutations involve conserved amino acid residues, are located within the cofactor binding domain, and are predicted by structural analysis to have a destabilizing effect. Yeast modeling and complementation studies validated the pathogenicity of the MECR mutations. Fibroblast cell lines from affected individuals displayed reduced levels of both MECR and lipoylated proteins as well as defective respiration. These results suggest that mutations in MECR cause a distinct human disorder of the mtFAS pathway. The observation of decreased lipoylation raises the possibility of a potential therapeutic strategy.
Keywords: Basal Ganglia; Cells, Cultured; Child; Child, Preschool; Dystonic Disorders; Fatty Acids; Female; Fibroblasts; Genetic Complementation Test; Humans; Infant; Male; Mitochondria; Mitochondrial Diseases; Models, Molecular; Mutation; Mutation, Missense; Optic Atrophy; Oxidoreductases Acting on CH-CH Group Donors; Pedigree; RNA Splice Sites; Saccharomyces cerevisiae